Impelentasi Kegiatan Bumi Gelisah dalam Menumbuhkan Minat Baca Siswa SDN Kondangjaya III - Amelia, Meilani; Putri, Noer Aisya Imelia; Puteriana, Adinda Rukman; Alpian, Yayan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to find out whether the Restless Earth program (Wednesday Thursday School Literacy Movement) can cultivate students' interest in reading at SDN Kondangjaya III. The research method used is descriptive qualitative. Data collection techniques include observation, interviews, and documentation. Data analysis techniques are carried out in three action steps: data reduction, data presentation, and conclusion. The results show that the Restless Earth program can cultivate students' interest in reading with positive support from the school and the role of teachers who are able to motivate students. The Restless Earth activity is carried out every Wednesday and Thursday for 15 minutes before learning begins. The books used are non-curricular books. Facilities provided by the school include the school library, reading corner, posters, and pictures related to reading activities.